3D Digital technology as an alternative educational tool in preclinical dentistry. (8th January 2022) - Yamakami, Shelyn Akari; Nagai, Manavi; Chutinan, Supattriya; Ohyama, Hiroe
Abstract: Introduction: The advancement of 3D digital scanners has allowed educators to uphold the quality of education whilst implementing novel methods of assessment. Objective: The purpose of this study was to compare two evaluation methods, conventional and digital scanned assessments, on student cavity preparations and students and faculty's perceptions of these assessment methods. Methods: Predoctoral students performed Class II amalgam and Class III resin composite preparations on simulated teeth for their preclinical competency examinations. Two calibrated faculty evaluated the students' preparations using dental instruments for conventional assessments and 3D scanned images for digital assessments. Faculty scores from both assessment methods were compared and statistically analysed ( p < .05). Students also self‐assessed their performance using the digital scanned images and filled out a perception survey. Results: There was no statistically significant difference between the conventional (Class II; 73.3 ± 12.2 and Class III; 82.5 ± 8.9) and the digital assessment with scanned images (Class II; 71.3 ± 11.0 and Class III; 82.2 ± 8.2). Faculty scores from both methods have shown a trend of comparability. Most students agreed that digital ideal preparation models were useful (84.2%) and almost all students agreed that digital technology helped them learn operative dentistry (91.1%). In contrast, most students agreed that conventional assessment should be the main self‐evaluation system (82.2%) and disagreed that digital assessment is more effective than conventional self‐assessment (68.3%). Conclusion: Our study demonstrated that 3D digital technology could be an alternative and/or supplementary educational tool to aid in upholding the quality of dental education.